Students’ Employability Skills: Development Strategies - R. R. Khuziakhmetov; G. F. Romashkina (Высшее образование в России)
The fundamental transition from the concept of maintaining employment to personnel mobility and employability, as well as the transformation of the working environment make the case for addressing the development of students’ employability skills. Job seekers are intended to be effective communicators and drive own productivity. It is important to understand how students perceive the employability skills, which are formed during the university period. The article aims to reveal strategies for employability skills development, implemented by master’s and doctoral students. These students have a long learning experience and acquire a higher level of qualifications. They are better prepared for employment, but still can face obstacles.The empirical base of the study consists of 50 interviews with students of Tyumen universities (32 master’s degree students and 18 doctoral students). The data were obtained through semi-structured interviews. The authors focused on 4 employability skills: communication, teamwork, self-management, and self-control. Three strategies of employability skills development are revealed. Active strategy: students identify employability skills as a resource, give average and higher self-assessments of their development, provide detailed examples of their use, analyze mistakes, and see opportunities for future development. Intermediate strategy: students also recognize the importance of employability skills, but there is an imbalance in the development of individual and interpersonal skills. In general, they give average self-assessments of skill development and provide insufficiently detailed descriptions of their use in practice. Their plans for developing employability skills are not precise. Passive strategy: students do not identify employability skills as a resource, and are not proactive in their improvement, limiting themselves to an abstract description of intention. The conclusion is substantiated that only a small part of students of regional universities identify individual and interpersonal skills as a resource and build long-term plans for their improvement.